Molecular insight into the high selectivity of double-walled carbon nanotubes - Kowalczyk, Piotr (Royal Society of Chemistry, 2012)
Combining experimental knowledge with molecular simulations, we investigated the adsorption and separation properties of double-walled carbon nanotubes (DWNTs) against flue/synthetic gas mixture components (e.g. CO2, CO, N2, H2, O2, and CH4) at 300 K. Except molecular H2, all studied nonpolar adsorbates assemble into single-file chain structures inside DWNTs at operating pressures below 1 MPa. Molecular wires of adsorbed molecules are stabilized by the strong solid–fluid potential generated from the cylindrical carbon walls. CO2 assembly is formed at very low operating pressures in comparison to all other studied nonpolar adsorbates. The adsorption lock-and-key mechanism results from perfect fitting of rod-shaped CO2 molecules into the cylindrical carbon pores. The enthalpy of CO2 adsorption in DWNTs is very high and reaches 50 kJ mol−1 at 300 K and low pore concentrations. In contrast, adsorption enthalpy at zero coverage is significantly lower for all other studied nonpolar adsorbates, for instance: 35 kJ mol−1 for CH4, and 14 kJ mol−1 for H2. Applying the ideal adsorption solution theory, we predicted that the internal pores of DWNTs have unusual ability to differentiate CO2 molecules from other flue/synthetic gas mixture components (e.g. CO, N2, H2, O2, and CH4) at ambient operating conditions. Computed equilibrium selectivity for equimolar CO2–X binary mixtures (where X: CO, N2, H2, O2, and CH4) is very high at low mixture pressures. With an increase in binary mixture pressure, we predicted a decrease in equilibrium separation factor because of the competitive adsorption of the X binary mixture component.We showed that at 300 K and equimolar mixture pressures up to 1 MPa, the CO2–X equilibrium separation factor is higher than 10 for all studied binary mixtures, indicating strong preference for CO2 adsorption. The overall selective properties of DWNTs seem to be superior, which may be beneficial for potential industrial applications of these novel carbon nanostructures.